Call the Doctor? Understanding Health Service Trends in New Brunswick, Part I, 1918–1950 - Mullally, Sasha; MacDonald, Katherine (Journal of New Brunswick Studies / Revue d’études sur le Nouveau-Brunswick, 2017)
This article initiates an online discussion of health service trends in New Brunswick over the course of the twentieth century. It sets the stage by describing changes in physician service access, examining registration data from the American Medical Directory for 1918 and 1950. When comparing data sets, three distinct trends emerge. First, we see the centralization of physician services in larger population centres, especially those communities with larger general hospitals. Second, a more equitable physician per population ratio between anglophone and francophone, southern and northern, regions of the province in 1950 as compared to 1918 is evident. Finally, the transnational Canada-U.S. border becomes more important in defining physician career paths (especially medical and post-graduate education) as the twentieth century unfolds.